2019
DOI: 10.1007/s40122-019-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Herpes Zoster and Postherpetic Neuralgia in China: Results from a Cross-Sectional Study

Abstract: IntroductionFew studies have examined the epidemiology of herpes zoster (HZ) and postherpetic neuralgia (PHN) in China. The aim of this study was to estimate the prevalence of HZ and PHN in China, and to examine the clinical characteristics of patients identified with PHN.MethodsThis was a cross-sectional study conducted in 24 hospitals in seven cities in China. Prevalence of HZ and PHN was determined by physician (n = 100) chart review of patients (n = 36,170) aged ≥ 40 years seeking medical care over a 30- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 31 publications
2
67
0
Order By: Relevance
“…Herpes zoster (HZ) is one of the leading causes of severe pain in China, with a prevalence estimated to be 7.7% of the population who seek medical care. Moreover, 29.8% of HZ patients may develop postherpetic neuralgia (PHN) that causes pain for months or even years (1). Neuropathic pain is well-understood to have a negative impact on the quality of life and a significant impact on cognitive function, including attention, memory, and executive functions (2).…”
Section: Introductionmentioning
confidence: 99%
“…Herpes zoster (HZ) is one of the leading causes of severe pain in China, with a prevalence estimated to be 7.7% of the population who seek medical care. Moreover, 29.8% of HZ patients may develop postherpetic neuralgia (PHN) that causes pain for months or even years (1). Neuropathic pain is well-understood to have a negative impact on the quality of life and a significant impact on cognitive function, including attention, memory, and executive functions (2).…”
Section: Introductionmentioning
confidence: 99%
“…Two cross-sectional studies, both conducted in mainland China, reported on the prevalence of HZ [9,19]. In the first study, the prevalence of physician-diagnosed HZ among 36,170 adults from 40 years presenting to 24 hospitals across China over a 30-to 60day period was 7.7% [19].…”
Section: Hz Age-distribution Incidence and Prevalencementioning
confidence: 99%
“…Two cross-sectional studies, both conducted in mainland China, reported on the prevalence of HZ [9,19]. In the first study, the prevalence of physician-diagnosed HZ among 36,170 adults from 40 years presenting to 24 hospitals across China over a 30-to 60day period was 7.7% [19]. The prevalence of HZ was 5.5% in 40-50 year olds, 7.1% in 51-59 year olds, 8.4% in 60-69 year olds, and 10.6% in those aged ≥70 years, and was similar in women (7.9%) and men (7.6%) [19].…”
Section: Hz Age-distribution Incidence and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of cases vary from region to region. For example, in China, the prevalence rate of PHN in patients with herpes zoster is 29.78% [26], and in Europe, it is 5.82% [6]. Therefore, clinicians can set up their own database according to their actual situation.…”
Section: Limitations and Deficienciesmentioning
confidence: 99%